RAGE pathway activation and function in chronic kidney disease and COVID-19 - Curran, Colleen S.; Kopp, Jeffrey B. (Frontiers in Medicine, 2022)
The multi-ligand receptor for advanced glycation end-products (RAGE) and its ligands are contributing factors in autoimmunity, cancers, and infectious disease. RAGE activation is increased in chronic kidney disease (CKD) and coronavirus disease 2019 (COVID-19). CKD may increase the risk of COVID-19 severity and may also develop in the form of long COVID. RAGE is expressed in essentially all kidney cell types. Increased production of RAGE isoforms and RAGE ligands during CKD and COVID-19 promotes RAGE activity. The downstream effects include cellular dysfunction, tissue injury, fibrosis, and inflammation, which in turn contribute to a decline in kidney function, hypertension, thrombotic disorders, and cognitive impairment. In this review, we discuss the forms and mechanisms of RAGE and RAGE ligands in the kidney and COVID-19. Because various small molecules antagonize RAGE activity in animal models, targeting RAGE, its co-receptors, or its ligands may offer novel therapeutic approaches to slowing or halting progressive kidney disease, for which current therapies are often inadequate.